A survey of research on nightglow variability - Forsyth,RJ; Wraight,PC (Planetary and Space Science, 1987)
The literature from 1970 to 1987 on nightglow variability, particularly from the mesosphere and lower thermosphere, is surveyed and classified. Earlier work is referenced via reviews. The work is classified both in terms of its coverage of short period, diurnal and long term variations, and also by the observational methods used. © 1987.